Thyroid function and hepatic fibrosis/cirrhosis: a two-sample Mendelian randomization study - Wang, Yan; Zhang, XiaoLi; Li, Qin; Zhang, Qing; Liu, Jun (Frontiers in Genetics, 2025)
BackgroundEvidence on the relationship between thyroid function and hepatic fibrosis/cirrhosis are still unclear, with inconsistent conclusions. This Mendelian randomization (MR) study aimed to investigate the potential causal association between thyroid function and hepatic fibrosis/cirrhosis in order to provide new insights for improving prevention and control strategies for this disease.MethodsGenome-wide association study (GWAS) data on exposures, which included hyperthyroidism, hypothyroidism, and thyroid-stimulating hormone (TSH), were extracted from the MRC Integrative Epidemiology Unit (MRC-IEU) (https://gwas.mrcieu.ac.uk/), and GWAS data for outcomes, including hepatic fibrosis/cirrhosis and chitinase-3-like protein 1 (CHI3L1), were obtained from the FinnGen consortium (https://www.finngen.fi/fi). Inverse variance weighted (IVW), weighted median, and MR-Egger methods were utilized to examine the causal association between thyroid function and the risk of hepatic fibrosis/cirrhosis. Cochran’s Q test was used to assess the heterogeneity of instrumental variables (IVs), while MR-PRESSO and leave-one-out analyses were conducted for sensitivity analysis.ResultsIVW estimates suggested that hypothyroidism had a potential causal association with higher odds of hepatic fibrosis/cirrhosis (OR = 1.247, 95% CI: 1.087–1.431). Leave-one-out results indicated that this potential causal relationship was relatively robust. In addition, we assessed the causal association between hypothyroidism and hepatic fibrosis/cirrhosis before and after removal of outliers with heterogeneity. After removing the outliers, the association was still significant (OR = 1.266, 95% CI: 1.082–1.482, P = 0.0046).ConclusionPatients with hypothyroidism may have a higher risk of hepatic fibrosis/cirrhosis, and this finding may provide some references for the early screening and prevention of the disease. However, further studies are needed to explore the specific mechanisms by which hypothyroidism influences hepatic fibrosis/cirrhosis.